2019
DOI: 10.1039/c9nj04232f
|View full text |Cite
|
Sign up to set email alerts
|

Red-emissive nitrogen doped carbon quantum dots for highly selective and sensitive fluorescence detection of the alachlor herbicide in soil samples

Abstract: We report the synthesis of red-emissive nitrogen-doped carbon quantum dots and their applications in the highly selective and sensitive detection of the alachlor herbicide in soil samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The detailed information on N1s was shown in Figure 1 g, which was split into two peaks at 398 eV (N-C-N) and 398.6 eV (N-H), respectively [ 36 ]. The high-resolution spectrum of S2p ( Figure 1 h) revealed the presence of the C = S bond (166.8 eV) in RCDs [ 37 ]. These results further confirmed the success of S element doping in RCDs.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed information on N1s was shown in Figure 1 g, which was split into two peaks at 398 eV (N-C-N) and 398.6 eV (N-H), respectively [ 36 ]. The high-resolution spectrum of S2p ( Figure 1 h) revealed the presence of the C = S bond (166.8 eV) in RCDs [ 37 ]. These results further confirmed the success of S element doping in RCDs.…”
Section: Resultsmentioning
confidence: 99%
“…Du, Cheng, Lai, Ruan, and Zhao (2019) synthesized red‐emissive nitrogen‐doped carbon quantum dots (N‐CQDs) by hydrothermal treatment of p‐phenylenediamine (p‐PD) for fluorescence detection of the alachlor herbicide. After method optimization, good linearity between 0.005 and 150 μM and a low LOD of 0.2 nM were obtained.…”
Section: Chemiluminescence and Fluorescence Methodsmentioning
confidence: 99%
“…Fuyou Du et al showed that fluorescence and emission intensity change with a change in solvent; that is, carbon dots exhibit solvent-dependent photoluminescence. 110…”
Section: Solventmentioning
confidence: 99%
“…The developed NCD probe demonstrated exceptional stability, sensitivity and selectivity, and outstanding repeatability in the sensing of alachlor, and it can measure alachlor over a broad concentration range (0.005-150 M). 110 To veterinary medicines, red emissive CDs demonstrate a rapid, sensitive, and targeted fluorescence response. Animals that are slaughtered for food are treated with veterinary medicines to prevent or cure illness; food made from these treated animals may include traces of these drugs which are harmful for human consumption.…”
Section: Biosensingmentioning
confidence: 99%